Improving research-policy linkages in Nigeria - Aberman, Noora-Lisa; Schiffer, Eva; Johnson, Michael E.; Oboh, Victor (International Food Policy Research Institute, 2010)
When there is disconnect between research and policy, high quality research-based information can be produced without impact on policy dialogue and action. This often results in policy actions lagging far behind scientific and academic knowledge, the presence of avoidable inefficiencies in policy design and implementation, and policies that may not fulfill their purpose. While there is no real consensus on how to successfully improve linkages between research and policy, it is clear that understanding the specific context in which policy decisions take place is critical. To better understand the dynamics between agricultural research and policymaking in Nigeria, we examined the 2006 National Fertilizer Policy for Nigeria and the process that led to its writing and adoption.